Development of nonlinear CAD Models for the design of linear LDMOS power amplifiers - Du Plessis, Francois Daniel (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.